Avian Hepatitis B Virus Infection Is Initiated by the Interaction of a Distinct Pre-S Subdomain with the Cellular Receptor gp180 - Urban, Stephan (American Society for Microbiology, 1998)
Functionally relevant hepadnavirus-cell surface interactions were investigated with the duck hepatitis B virus (DHBV) animal model by using an in vitro infection competition assay. Recombinant DHBV pre-S polypeptides, produced in Escherichia coli, were shown to inhibit DHBV infection in a dose-dependent manner, indicating that monomeric pre-S chains were capable of interfering with virus-receptor interaction. Particle-associated pre-S was, however, 30-fold more active, suggesting that cooperative interactions enhance particle binding. An 85-amino-acid pre-S sequence, spanning about half of the DHBV pre-S chain, was characterized by deletion analysis as essential for maximal inhibition. Pre-S polypeptides from heron hepatitis B virus (HHBV) competed DHBV infection equally well despite a 50% difference in amino acid sequence and a much-reduced infectivity of HHBV for duck hepatocytes. These observations are taken to indicate (i) that the functionality of the DHBV pre-S subdomain, which interacts with the cellular receptor, is determined predominantly by a defined three-dimensional structure rather than by primary sequence elements; (ii) that cellular uptake of hepadnaviruses is a multistep process involving more than a single cellular receptor component; and (iii) that gp180, a cellular receptor candidate unable to discriminate between DHBV and HHBV, is a common component of the cellular receptor complex for avian hepadnaviruses.